Epistemologi Syed Hossen Nasr dalam Pendidikan Islam - Eko Nani Fitriono (Sekolah Tinggi Ilmu Tarbiyah (STIT) Syekh burhanuddin, 2022)
This study wants to provide insight into the importance of Seyyed Hossein Nasr’s thoughts in the Islamic world. Behind the thoughts of Seyyed Hossein Nasr, to know ethics and morality, and to find out the thoughts of Seyyed Hossein Nasr about ethics. This research uses library research with a philosophical approach to figures. The data collection method used is the documentation method with primary sources from Nast’s various works related to the discussion. The data that has been collected is then analyzed using descriptive analysis methods. Based on the author’s findings, Nasr’s thoughts about human beings are always in the context of kutik towards the modern world. Judging from the process of its creation, humans are created from two components of body and spirit. The human concept according to Nast is applied in the world of education in order to develop the spiritual dimension and human potentials, especially in the context of Islamic education goals. This is because spirituality and the potentials possessed by humans can be specifically processed and developed in more concrete forms, namely in the realm of Islamic educational goals. At the same time, the goals of Islamic education are formulated to reach a spiritual level and develop human potentials. It was at this point that the human concept in Hossein Nast’s thought was manifested in the goals of Islamic education, and at the same time the objectives of Islamic Religious Education were to get an explanation and at the same time its foundation from Nast’s ideas about Humans.